2020
DOI: 10.1371/journal.pone.0228019
|View full text |Cite
|
Sign up to set email alerts
|

Adult health burden and costs in California during 2013 associated with prior adverse childhood experiences

Abstract: ObjectivesTo estimate the adult health burden and costs in California during 2013 associated with adults' prior Adverse Childhood Experiences (ACEs). MethodsWe analyzed five ACEs-linked conditions (asthma, arthritis, COPD, depression, and cardiovascular disease) and three health risk factors (lifetime smoking, heavy drinking, and obesity). We estimated ACEs-associated fractions of disease risk for people aged 18+ for these conditions by ACEs exposure using inputs from a companion study of California Behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 62 publications
(59 reference statements)
1
26
0
Order By: Relevance
“…Using 2017 BRFSS data from TN and VA, this study aimed to show the economic impact of exposure to any ACE to an associated medical cost or DALYs burden for several adulthood health outcomes, health risk factors, and chronic health conditions. Consistent with other studies, the current study found attributable risks due to exposure to any ACEs for arthritis, COPD, depression, obesity, smoking, and alcohol use (Miller et al, 2020;Sidmore, 2018;Sycamore Institute, n.d.). An analysis of 2013 BRFSS data by Sidmore showed a population attributable risk (PAR) between ACEs and frequent mental distress, COPD, emphysema, chronic bronchitis, increased days of poor physical health, smoking, asthma (current or former), diabetes, heavy alcohol consumption, obesity, increased activity limitation, diagnosis of arthritis, insufficient sleep, and separation or divorce in Alaska (Sidmore, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Using 2017 BRFSS data from TN and VA, this study aimed to show the economic impact of exposure to any ACE to an associated medical cost or DALYs burden for several adulthood health outcomes, health risk factors, and chronic health conditions. Consistent with other studies, the current study found attributable risks due to exposure to any ACEs for arthritis, COPD, depression, obesity, smoking, and alcohol use (Miller et al, 2020;Sidmore, 2018;Sycamore Institute, n.d.). An analysis of 2013 BRFSS data by Sidmore showed a population attributable risk (PAR) between ACEs and frequent mental distress, COPD, emphysema, chronic bronchitis, increased days of poor physical health, smoking, asthma (current or former), diabetes, heavy alcohol consumption, obesity, increased activity limitation, diagnosis of arthritis, insufficient sleep, and separation or divorce in Alaska (Sidmore, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The differences between the current study and the study done in CA could be due to disparities in costs between the states; the CA study did not calculate DALYs 420,902 114,734 127,513 15,469,993,515 20,276,379,560 646,945,848 942,089,507 for drinking, smoking or obesity; and the current study could not calculate attributable risk for asthma or CVD for the population studied due to data limitations. The prevalence of exposure to ACEs was similar in the three states; CA 61%, (Miller et al, 2020), TN 59.1%, and VA 61.7%.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The economic costs of CA in terms of excess healthcare and other services (legal, social, etc.) take a huge toll on government spending, 45 46 and investing appropriately to combat CA will ultimately save societal costs. 11 12 42 Finally, governments could monitor the prevalence of CA in populations and consider reductions in reports of CA a priority in efforts to achieve Sustainable Development Goals.…”
Section: Discussionmentioning
confidence: 99%